The Relationship of Personal Hygiene and Contact History with the Incidence of Typhoid Fever in the Inpatient Room of Sari Asih Ciledug Hospital, Tangerang - Gustiana, Lina; Melastuti, Erna (Politeknik Kesehatan Kementerian Kesehatan Banten, 2026)
Background: Typhoid fever is an acute infectious disease of the gastrointestinal tract that remains a health problem in Indonesia and is closely related to personal hygiene and history of contact with patients. This study aims to determine the relationship between personal hygiene and history of contact with typhoid fever cases in the inpatient ward of Sari Asih Hospital, Ciledug, Tangerang. Methods: This study used a quantitative design with a cross-sectional approach. The study sample consisted of 44 respondents selected using purposive sampling. The research instruments included a personal hygiene questionnaire, a contact history observation sheet, and medical record data to determine the incidence of typhoid fever. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. Results: The results showed that there was a relationship between personal hygiene and the incidence of typhoid fever (p-value = 0.012; OR = 6.750) and that there was a relationship between contact history and the incidence of typhoid fever (p-value = 0.008; OR = 7.500). Respondents with poor personal hygiene and a history of direct contact had a higher risk of developing typhoid fever. Conclusion: The conclusion of this study is that personal hygiene and contact history are significantly associated with the incidence of typhoid fever. It is hoped that the results of this study can be used as a basis for improving health promotion and typhoid fever prevention efforts through improved personal hygiene and contact control.